A framework for buyer satisfaction in e-procurement in Indian scenario: an integrated ISM and SEM approach. (2018) - Gupta, Manish; Tripathi, Shubham
E-procurement is expected to enhance coordination between buyers and suppliers and result in significant mutual satisfaction and economic benefits. However, many organisations that have implemented e-procurement are highly uncertain about the extent to which the satisfactions are realised. In the present scenario, even though the overall benefits of such systems are established, there is a need to analyse different factors that lead to different levels of buyer satisfaction among different organisations. In this work the ISM model for buyer satisfaction is proposed which is further analytically validated with SEM using AMOS. The results of validation turned out in fair with the developed models for buyer satisfaction. The findings indicate that transparency, improved quality and fulfilling warranty have the maximum driving power whereas long-term relationship between buyer-supplier has the maximum driven power. It is furthermore validated in the paper that transparency, improved quality, and fulfilling warranty leads to commitment, cooperation and trust that further on results in long-term relationship.